2021
DOI: 10.1186/s12886-021-02165-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis and clinical application of iris circulation in ischemic retinal disease

Abstract: Background To evaluate quantitative changes in iris blood circulation in patients with ischemic risk. Methods This observational case-control study included 79 patients with diabetic retinopathy (DR) and retinal vein occlusion (RVO). The RVO group included 21 patients; the monocular proliferative diabetic retinopathy (PDR) group included 19 patients; the nondiabetic retinopathy (NDR) group included 18 patients; and the healthy control group include… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…We also discovered a diversity of blood ow indices in different areas of the iris in adults. The VAD and VSD of the pupillary margin were high, and those of the whole iris were relatively low (7)(8)(9). Afterward, we studied type 2 diabetes mellitus (T2DM) patients with different courses of DR and found that the vessel density of the pupillary margin increases with the severity of DR (9).…”
Section: Introductionmentioning
confidence: 99%
“…We also discovered a diversity of blood ow indices in different areas of the iris in adults. The VAD and VSD of the pupillary margin were high, and those of the whole iris were relatively low (7)(8)(9). Afterward, we studied type 2 diabetes mellitus (T2DM) patients with different courses of DR and found that the vessel density of the pupillary margin increases with the severity of DR (9).…”
Section: Introductionmentioning
confidence: 99%
“…We also discovered a diversity of blood flow indices in different areas of the iris in adults. The VAD and VSD of the pupillary margin were high and those of the whole iris were relatively low [7][8][9]. Afterward, we studied type 2 diabetes mellitus (T2DM) patients with different courses of DR and found that the vessel density of the pupillary margin increases with the severity of DR [9].…”
Section: Introductionmentioning
confidence: 99%